Activated Hepatic Stellate Cells Induce Tumor Progression of Neoplastic Hepatocytes in a TGF-β Dependent Fashion - MIKULA, M. (2006)
The development of hepatocellular carcinomas from malignant hepatocytes is frequently associated with intra- and peritumoral accumulation of connective tissue arising from activated hepatic stellate cells. For both tumorigenesis and hepatic fibrogenesis, transforming growth factor (TGF)-β signaling executes key roles and therefore is considered as a hallmark of these pathological events. By employing cellular transplantation we show that the interaction of neoplastic MIM-R hepatocytes with the tumor microenvironment, containing either activated hepatic stellate cells (M1-4HSCs) or myofibroblasts derived thereof (M-HTs), induces progression in malignancy. Cotransplantation of MIM-R hepatocytes with M-HTs yielded strongest MIM-R generated tumor formation accompanied by nuclear localization of Smad2/3 as well as of β-catenin. Genetic interference with TGF-β signaling by gain of antagonistic Smad7 in MIM-R hepatocytes diminished epithelial dedifferentiation and tumor progression upon interaction with M1-4HSCs or M-HTs. Further analysis showed that tumors harboring disrupted Smad signaling are devoid of nuclear β-catenin accumulation, indicating a crosstalk between TGF-β and β-catenin signaling. Together, these data demonstrate that activated HSCs and myofibroblasts directly govern hepatocarcinogenesis in a TGF-β dependent fashion by inducing autocrine TGF-β signaling and nuclear β-catenin accumulation in neoplastic hepatocytes. These results indicate that intervention with TGF-β signaling is highly promising in liver cancer therapy.